STUDY OF THE DEVELOPMENT AND HISTORY OF THE METHODOLOGY OF TEACHING MATHEMATICS IN HIGHER EDUCATION (Conferencea, 2023)
Is in this article. What mathematics studies (object) consists of the spatial forms of available things-in matter and the quantitative relationships between them. The main task of teaching mathematics is to ensure that students firmly and consciously acquire the system of mathematical knowledge and skills necessary in everyday life and professional activities.